UTILIZATION OF SHELL FLOUR AS SUPPLEMENTS IN POULTRY AT JALAN VILLAGE, IDI RAYEUK, ACEH TIMUR - Rahmatul Fajri; Nurviana Nurviana; Dewi Novianti; Jofrishal Jofrishal (LPPM dan PM Universitas Samudra, 2022)
Improving the quality of egg production at Dusun Dulhok, Gampong Jalan Village, Idi Rayeuk was conducted in the form of training. This activity aims to provide understanding in the technique of processing shellfish into decent and safely flour to poultry. The stages of the activity are carried out by preparing basic materials taken at the shoreline of Tanjong Kapai Village and Keutapang Mameh which are adjacent to the training place. Monitoring and evaluation is needed to see the benefits, sustainability and impact of the training activities. During the activity, the community was enthusiastic in listening to the material presentation, they were actively involved in the discussion. During the mentoring process the community is eager to do each step in accordance with the instructions from the speaker. The community have a good commitment to applying the results of the training. At last we hope the training process is able to increase public awareness to improve the quality of poultry farming and improve the people’s economy.